THE REALIZATION THEME AND RHEME IN MANDAILING SONG TEXTS - Shoufi Nisma Dewi; Amrin Saragih; Anni Holila Pulungan (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This article discuss about realization of Theme and Rheme in Mandailing song texts by Odang and Masdani. The objectives of this study are describe about realization of Theme and Rheme especially Theme and Rheme in Mandailing songs text. The song text is by Odang and Masdani,. The sources of the data was taken from the video recorded. The data of this article is lyric as a text that contain Theme and Rheme. The data analysis found six pattern of realization of Theme and Rheme used in Mandailing song texts of Odang and Masdani. Andin this study did not find pattern Theme and Rheme unity to Theme and Theme and Rheme unity to Rheme.